ANALISIS TIPE BUDAYA POLITIK MASYARAKAT SUKU AKIT DESA BANTAN TENGAH KECAMATAN BANTAN KABUPATEN BENGKALIS - Lely Fitriana; Sri Erinda; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is motivated by the many people of the Akit people who do not understand political problems, so that many parties are not responsible for abusing the situation. The formulation of the problem in this study is "What are the Types of Political Culture of the Akit Tribe of Bantan Tengah Village in Bantan District of Bengkalis Regency and the Factors That Cause the Type of Political Culture of the Akit Tribe of Bantan Tengah Village of Bantan District". This study aims to determine What Type of Political Culture of the Akit Tribe of Bantan Tengah Village Bantan District of Bengkalis Regency and Factors That Cause the Type of Political Culture of the Akit Tribe of Bantan Tengah District of Bantan District. Researchers do not use the term population, only using the term sample this is due to researchers using a purposive sampling technique, namely the determination of the sample technique with consideration or certain criteria and researchers using a sample of 10 people from the Akit people. This research was conducted in Bantan District, Bengkalis Regency, conducted in June to July 2019. This research used a qualitative descriptive approach and the data collection techniques used Observation, Interview and Documentation, and data analysis techniques were carried out through the stages of reduction, data presentation, and drawing conclusions So in this research, it is proven that the Akit community has a type of political culture, that is, the community has low political participation and the factors that influence the type of political culture of the Akit community are the education level, the economic level and the communication media.Key Words : Types of Political Culture, Akit Tribes